CULTURAL MEMORY AND VISUAL BRANDING IN TRADITIONAL CULINARY DISPLAY OF URBAN BANDUNG - Gema Ariprahara; Sunarmi; Handriyotopo (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2026)
This study investigates Padang Ampera restaurants in Bandung as visual archives of Minangkabau cultural memory, navigating urbanization and consumer culture through visual branding. Using a qualitative interdisciplinary approach integrating cultural memory, visual branding, and urban design, it examines design elements like façades, paluang, and ornamentation in Bunga Tanjung, Salero Bagindo, and Saudara Kembar. Findings reveal that these elements enhance authenticity and emotional resonance, preserving Minangkabau identity while appealing to urban lifestyles. The study proposes a cultural branding model that weaves memory, identity, and storytelling, contributing to design practices that balance heritage and modernity. This model supports sustainable cultural preservation in urban culinary spaces but is limited by its focus on Bandung, suggesting broader regional studies. The research advances understanding of how visual branding and culinary display sustain cultural heritage in dynamic urban contexts